ANTIBIOTIC RESISTANCE IN CIMANUK RIVER, GARUT REGENCY, WEST JAVA - Syamsudin, Raden Aldizal Mahendra Rizkio; Sudjana, Shifa Nisrina; Nuari, Doni Anshar (Jurusan Farmasi, Poltekkes Kemenkes Palembang, 2024)
Background: Antibiotic resistance could causing infectious treatment by antimicrobial agent become not effective anymore. This could result in longer care and higher cost for patient. This research aimed to understand antimicrobial resistance from microbe isolated from Cimanuk River, Garut Residence, West Java Province. Methods: Antibiotic resistance testing in river water was conducted by isolating bacteria into enrichment TSB media and then Blood Agar and also MacConkey Agar by spread plate method. Sample then incubated in 37 °C for 24 hours to gain growing bacterial colony. Colony identification and antibiotic resistance testing was done using BD Phoenix 50. Results: Result showed that 50% E. coli bacterial isolate from Cimanuk River already developed resistance to Ampicillin, Piperacillin-Tazobactam, and Tetracycline antibiotic. Conclusion: Antibiotic resistance already occurred in E. coli bacteria isolated from Cimanuk River